PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AL- QUR’AN HADITS KELAS XI AGAMA DI MAN 10 JOMBANG - sriwahyuni -; Umi Chaidaroh; Emi Lilawati (JoEMS (Journal of Education and Management Studies), 2020)
Mind Mapping learning model is creative, effective, and literally recorded way to “map” thoughts. While student learning achievement is the result (mastery) achieved by students in a particular field of study after following the teaching dan learning process in a school. As for the problem to be investigated, is there any influence of the mind mapping method on student achievement in the Al-Qur’an Hadits subjects in class XI Religion students at MAN 10 Jombang. This study aims: 1) understand the implementation of the mind mapping method in the subject of the Qur’an in the XI religion students in MAN 10 Jombang. 2) to understand the results/ evaluation of student learning achievement in Al-Qur’an Hadith subjects in class XI Religion in MAN 10 Jombang. 3) to understand the effect of mind mapping learning methods on student achievement in Al-Qur’an subject Hadith in class XI Religion students at MAN 10 Jombang. The research design is field research through the correlational quantitative approach. The method of determining subject is take all of the class XI Agama. in MAN 10 Jombang as the respondents of the research which amounts to 22 students that consist of 22 class XI religion. For the population, the researcher takes class XI Agama students to become respondents